2003
DOI: 10.1080/14634980301489
|View full text |Cite
|
Sign up to set email alerts
|

Autotrophic picoplankton in Lake Baikal: Abundance, dynamics, and distribution

Abstract: The autotrophic picoplankton of Lake Baikal was discovered more than 30 years ago; the productivity of the endemic member of the group, Synechocystis limnetica, is of particular interest. In the course of long-term investigations, the abundance of this species was established using the sedimentation technique. Maximum abundance was reached at 104 cells per ml in summer. In addition to estimating the distribution of this species throughout a defined lake area during the spring-summer period, the character of in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 7 publications
3
31
0
Order By: Relevance
“…Picocyanobacteria are the predominant primary producers in pelagic Lake Baikal during summer (Nagata et al 1994;Goldman et al 1996;Belykh and Sorokovikova 2003;Katano et al 2005). A general explanation for the predominance of picocyanobacteria in oligotrophic lakes is that they have an advantage in the uptake of low concentration nutrients because of their high surface-to-volume ratio (Weisse 1993;Raven 1998).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Picocyanobacteria are the predominant primary producers in pelagic Lake Baikal during summer (Nagata et al 1994;Goldman et al 1996;Belykh and Sorokovikova 2003;Katano et al 2005). A general explanation for the predominance of picocyanobacteria in oligotrophic lakes is that they have an advantage in the uptake of low concentration nutrients because of their high surface-to-volume ratio (Weisse 1993;Raven 1998).…”
Section: Discussionmentioning
confidence: 99%
“…The vernal maximum biomass of phytoplankton in a Melosira year is about tenfold greater than that in a non-Melosira year (Bondarenko and Evstafyev 2002). Another characteristic of Lake Baikal is the dominance of very small phytoplankton, called picoplankton (formerly called ultrananoplankton) in the biomass and primary productivity of the phytoplankton assemblage (Votintsev et al 1972;Back et al 1991;Nagata et al 1994;Bondarenko et al 1996;Watanabe and Drucker 1999;Belykh and Sorokovikova 2003;Yoshida et al 2003;Katano et al 2005).…”
Section: Introductionmentioning
confidence: 98%
“…Also, nutrients decline to undetectable concentrations (Fig. 7a,b), mainly because of picoplankton growth (Nagata et al 1994;Belykh and Sorokovikova 2003;. Therefore, a resting stage helps A. skvortzowii survive these unfavorable conditions but successful sporulation depends on having sufficient time to switch resources and prepare for dormancy.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies on the abundance of picophytoplankton in Lake Baikal demonstrated that picocyanobacteria are also important components in terms of cell density among picophytoplankton (Boraas et al 1991;Nagata et al 1994;Watanabe and Drucker 1999;Belykh and Sorokovikova 2003;Nakano et al 2003;Katano et al 2005b;Belykh et al 2006). Picocyanobacteria are abundant throughout the entire lake during summer (Belykh and Sorokovikova 2003), with a maximum density of 2 9 10 6 cells ml -1 recorded in the southern basin (Nagata et al 1994).…”
Section: Introductionmentioning
confidence: 97%
“…The cell is of a slightly larger size (ca. 1.25 lm, according to Belykh and Sorokovikova 2003) as compared to unicellular picocyanobacterial cells (0.6-0.8 9 0.8-1.2 lm, according to Nagata et al 1994). Most picocyanobacteria are small unicellular organisms, and their shape is coccoid or that of a short rod (Belykh and Sorokovikova 2003).…”
Section: Introductionmentioning
confidence: 99%